THE ECONOMY OF UZBEKISTAN: GROWTH, CHALLENGES, AND PROSPECTS - Urunova Maftuna Gayratovna (Bright Mind Publishing, 2025)
This article provides a comprehensive analysis of Uzbekistan’s economy, tracing its evolution from a Soviet republic to an emerging market characterized by structural reforms and rapid growth. It examines key sectors including agriculture, manufacturing, energy, and services, and evaluates the impact of government policies on economic diversification, foreign investment, and poverty reduction. By exploring the challenges of regional disparities, labor market dynamics, and sustainability, the article offers insights into Uzbekistan’s prospects for inclusive and resilient development.
Keywords: Uzbekistan economy, economic reforms, foreign direct investment, agricultural sector, manufacturing, service sector, macroeconomic stability, poverty reduction, sustainability, regional development.